Handbook of research on information communication technology policy : trends, issues and advancements - Adomi, Esharenana E. (Information Science Reference, 2011)
"This book is a source book on information communication technology policies for those involved in ICT policy formulation, implementation, adoption, monitoring, evaluation and application"--Provided by publisher
Keywords: Information technology -- Government policy -- Developing countries -- Case studies; Telecommunication policy -- Developing countries -- Case studies